“Things Change but the Amerecano Is Here to Stay”: America in Italian Popular Movies of the 1980s - Zangari, Sostene M. (Review of International American Studies, 2013)
Sostene M. Zangari University of Milan Italy “Things Change but the Amerecano Is Here to Stay”: America in Italian Popular Movies of the 1980s The article focuses on a number of film comedies of the early 1980s. In different ways, the movies rearticulate the relationship between Italy and the United States. In showing how Italians can beat Americans at sports, how they can indulge in conspicuous consumption and finally how even the United States are not alien to provincialism and backwardness, these movies express a new mood of confidence that was widely felt in Italian society at the time. However, these movies came at a moment when the Italian film industry was on the verge of its decline. Starting from the 1980s, in fact, American movies and distributors would colonize the Italian movie market and depress the Italian movie industry.